The fate of camptothecin glycoconjugate: report of a clinical hold during a phase II study of BAY 56-3722 (formerly BAY 38-3441), in patients with recurrent or metastatic colorectal cancer resistant/refractory to irinotecan - Slingerland, Marije (Springer US, 2011)
Introduction BAY 56-3722 (formerly BAY 38-3441) is a glycoconjugated campthotecin, which was considered an attractive drug to assess in colorectal cancer (CRC). Patient and methods Phase II study design evaluating the antitumor activity of BAY 56-3722 IV 320 mg/m(2) daily for 3 days every 3 weeks in patients with recurrent or metastatic inoperable CRC resistant to irinotecan. Results Twenty-four patients received the study treatment. Triggered by adverse events in two other studies with this compound the study was put on a clinical hold while the safety data were reviewed for the entire program. After the review Bayer decided to withdraw BAY 56-3722 from all clinical investigations. Discussion We felt it was our obligation to share this interrupted phase II study for two reasons: to report the fate of camptothecin glycoconjugate and to report the unique situation of a clinical hold during a phase II study.